THE INFLUENCE OF SUSTAINABLE SUPPLY CHAIN MANAGEMENT ON PERFORMANCE OF ORGANIC COFFEE IN PASURUAN REGENCY - Nikmah Husnaeni; Dwi Retnoningsih (Socio-Economics/Agribusiness Department, 2021)
Pasuruan Regency is the largest area of organic coffee in East Java, Indonesia that has a potential future competitive advantage, but organic coffee is currently still weak and has to compete with non-organic coffee and imported coffee. Increase competition and make a business become sustainable require the involvement of actors in the supply chain and sustainable principles. This study aims to analyze the influence of supply chain sustainable management on performance in organic coffee in Pasuruan Regency. This research conducted in Prigen and Tutor Districts, Pasuruan Regency, East Java, in March until April 2020. The data was gathered from 51 respondents who were determined using purposive sampling and the Rules of Thumb with SEM-PLS as the analysis technique. Based on SEM-PLS analysis, sustainable supply management practices have a sustainable positive effect on sustainable performance, except for sustainable supplier management on social performance and sustainable consumer management on environmental performance. This is due to the lack of involvement of all suppliers in the social activities of the community and consumers who are not oriented towards the environmental aspects of organic coffee.